2006
DOI: 10.1016/j.rmed.2005.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Home mechanical ventilatory support in patients with restrictive ventilatory disorders: A 48-year experience

Abstract: Long-term home mechanical ventilatory support by both NPV and positive pressure ventilation is effective in patients with IK, PP syndrome, and a M group, even after a period of 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 33 publications
1
25
1
2
Order By: Relevance
“…A similar 10-fold increase was noted in the northern Netherlands but over a longer time period (1980 -2004). 22 The most significant increase in HMV use in developed countries took place in the 1990s. In the first decade of the 21st century, the increase was still preserved, but was much slower, reaching an annual 2-3-fold increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar 10-fold increase was noted in the northern Netherlands but over a longer time period (1980 -2004). 22 The most significant increase in HMV use in developed countries took place in the 1990s. In the first decade of the 21st century, the increase was still preserved, but was much slower, reaching an annual 2-3-fold increase.…”
Section: Discussionmentioning
confidence: 99%
“…Laub and Midgren 26 reported that subjects who had started HMV in an acute setting were more likely to be ventilated via tracheostomy than subjects qualified electively. Moreover, the long-term retrospective observational study performed by Duiverman et al 22 suggested a worse prognosis for subjects in whom HMV was implemented on an acute basis. In Poland, a rapid decrease in the proportion of tracheostomized subjects began in 2007 due to the increased number of HMV cases initiated in respiratory departments.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,13,19,20 Therefore, when identifying predictive risk factors, parameters observed after NIV initiation appear more valuable and reliable than those observed before the commencement of NIV. 18,20,22 We previously showed that P aCO 2 measured a few months after the start of long-term NIV is a possible prognostic factor in subjects with both restrictive thoracic disease 18 and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Arterial blood gases (ABGs) stabilize a few months after NIV initiation, and are sustained for many years in sub-jects with both COPD 10,18 and restrictive thoracic disease. 10,12,13,19,20 We previously showed that the average P aCO 2 of subjects breathing spontaneously decreases rapidly within several weeks of NIV, and thereafter increases gradually throughout long-term NIV. 18,20 We hypothesized that the adaptive mechanism that permits chronic hypercapnia occurs even in subjects receiving long-term NIV.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation